Pengaruh Penambahan Serat Kawat Bendrat Berbentuk “U” Terhadap Sifat Mekanis Beton - Irvan, Ridho Kurnia Putra; Ismeddiyanto, Ismeddiyanto; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Concrete is the main ingredient in the construction world, because the concrete is easy to work and economical in terms of cost, but the concrete is considered to have low tensile strength compared with the compressive strength, so the need for effort in improving the mechanical properties of the concrete mixing fiber in concrete mixture is wrong One attempt to improve the mechanical properties of concrete one of them by using fiber wire bedrators formed into